Analysis and Development of Surface Distress Index Modified Based on Pavement Condition Index Criteria for Pavement Evaluation - Gerardo, Faisal; Subagio, Bambang S.; Frazila, Russ B.; Wibowo, R. Sony Sulaksono (Salehan Institute of Higher Education, 2025)
The surface distress index (SDI) method has been used in Indonesia to assess road conditions, especially for areas with limited access, inadequate equipment, and limited local resources, which cause inaccuracies in the resulting pavement condition assessment. This research aims to develop a more accurate and efficient pavement condition assessment model based on three types of damage: cracks, potholes, and rutting. To generate accurate SDI values, we adopt and modify the deduct value (DV) curve based on the PCI method to determine the corresponding damage weight and the new road condition assessment. Based on the research results, the three modified SDI damage models showed an average accuracy value of 90%, which means that there is a good match between the models and the conditions on the ground, which is reinforced by the analysis of the mean absolute percentage error (MAPE) and root mean squared error (RMSE) values. In addition, the resulting development includes new assessment criteria and parameters, such as customized DV curve models and specific damage equations, condition index, condition rating, and maintenance types. Which in turn can support more effective and efficient infrastructure management and maintenance. Doi: 10.28991/CEJ-2025-011-01-014 Full Text: PDF